Chronic shoulder pain – a rare presentation of renal cell carcinoma: a case report (BIRDEM Medical Journal, 2024)
Renal cell carcinoma is a common malignancy and may present with metastatic disease. While metastasis to bones is common, it is uncommon to be the predominant presenting feature. Here, we present case history of a 40-year-old man suffering from chronic regional shoulder pain that poorly responded to medications and physiotherapy and later diagnosed as metastatic renal cell carcinoma. This case stresses that chronic monoarthritis or regional pain syndromes, without an obvious aetiology and poor response to symptomatic and general measures, should guide for an in-depth investigation to find the aetiology.BIRDEM Med J 2024; 14(2): 108-111